Metformin use and risk of lactic acidosis in people with diabetes with and without renal impairment: a cohort study in Denmark and the UK. Issue 4 (19th September 2016) - Li, L.; Jick, S.; Gopalakrishnan, C.; Heide‐Jørgensen, U.; Nørrelund, H.; Sørensen, H. T.; Christiansen, C. F.; Ehrenstein, V.
Abstract: Aims: To assess risk of lactic acidosis among metformin users compared with other glucose‐lowering agent users, according to renal function. Methods: Using routine registries and databases, we conducted a cohort study. Of 43 580 metformin and 37 788 other glucose‐lowering agent users in northern Denmark and 102 688 metformin and 28 788 other glucose‐lowering agent users in the UK during 2001–2011, we identified lactic acidosis using diagnostic codes. We calculated the incidence rates of lactic acidosis in metformin and other glucose‐lowering agent users overall and according to baseline estimated GFR (eGFR) levels. Results: In Denmark, the incidence rates of lactic acidosis were 11.6 (95% CI 7.0–18.1) and 1.8 (95% CI 0.4–5.4) per 100 000 person‐years of metformin use and of other glucose‐lowering agent use, respectively. In the UK, the corresponding lactic acidosis incidence rates were 6.8 (95% CI 4.6–9.6) and 1.0 (95% CI 0.01–5.7) per 100 000 person‐years of metformin use and of other glucose‐lowering agent use. The incidence rates increased with decreasing baseline eGFR in both countries. Of the metformin‐exposed people with lactic acidosis, 37% in Denmark and 34% in the UK experienced a decline in renal function in the year before the diagnosis. Conclusions: Risk of lactic acidosis was higher in metformin users than in other glucose‐lowering agent users, and increased with decreasing eGFR, although this could be attributable to surveillance bias; however, diagnosed lactic acidosis was rare and can occur regardless of renal function. What's new?: In Denmark, the incidence rates of lactic acidosis were 11.6 and 1.8 per 100 000 person‐years of metformin use and use of other glucose‐lowering agents, respectively. In the UK, the corresponding incidence rates were 6.8 and 1.0 per 100 000 person‐years. Incidence rates of metformin‐exposed lactic acidosis increased with decreasing baseline estimated GFR (eGFR) in both countries; however, lactic acidosis can occur regardless of renal function. Of metformin‐exposed people with lactic acidosis, 37% in Denmark and 34% in the UK had experienced a decline in renal function in the year before the diagnosis compared with the baseline estimated GFRs.